Village Website Development for Information Transparency and Tourism Promotion in Panton Kabu Village - Ernawati Ernawati; Hasanuddin Husin; Vina Liza Yanti; Marniati; Sri Handayani; Arfriani Maifizar; Jasmi; Darmawan (Jurnal Pengabdian Mitra Indonesia, 2026)
Digital transformation at the village level has become an important strategy in improving public information services, administrative transparency, and local potential promotion. Panton Kabu Village, located in Panga District, Aceh Jaya Regency, has tourism potential through Ceuraceu Waterfall and various local products, but information dissemination was still conducted conventionally, limiting public access to information and village promotion. This community service activity aimed to develop a village website as a digital platform for information transparency and tourism promotion. The implementation used a participatory approach through village observation and data collection, website structure planning, website design and development, content input, website testing and evaluation, and website publication. The developed website contains village profiles, village services, news and infographics, activity documentation, and information about village tourism and local products. The results showed that the village website was successfully developed and accessible through computers and mobile devices. The website improved public information accessibility, supported transparent village governance, and expanded digital promotion of tourism and village potential. This program is expected to support sustainable village digitalization and strengthen village governance through information technology.